Factors Associated with Caregiver Sleep Quality Related to Children with Rare Epilepsy Syndromes - Dale C. Hesdorffer, PhD; Barbara L. Kroner, PhD; Jing Shen, PhD; Kathleen Farrell, MB, BCh, BAO; Steve Roberds, PhD; Brandy Fureman, PhD; Brianne McDonald; Lynn Egan; Monika Jones; Monica Weldon; Michael Harris; Kim Rice; et al. (The Journal of Pediatrics: X, 2020)
Objective: To evaluate the impact of pediatric sleep disturbances and night-time seizure monitoring of children with rare epilepsy syndromes on the sleep quality and mental health of caregivers. Study design: A cross-sectional study was conducted using caregiver entered data from the Rare Epilepsy Network on pediatric sleep disturbances and Patient Reported Outcomes Measurement Information System measures for caregiver fatigue, sleep disturbance, sleep-related impairment, depression, anxiety, companionship, and cognition. Logistic regression was used to examine associations between risk factors and caregiver sleep quality. Results: Non-Hispanic white mothers comprised 83% of the 742 respondents in this study. After adjusting for covariates, difficulty falling asleep, excessive daytime sleepiness, frequent night-time awakenings, and very restless sleep in children were associated with fatigue (aOR 95% CI, 1.5-2.2), sleep-related disturbance (aOR 95% CI, 1.7-2.6) and sleep impairment (aOR 95% CI, 1.5-2.4) in caregivers. Caregiver anxiety (aOR 95% CI, 3.6-6.0) and depression (aOR 95% CI, 2.8-6.0) were also highly associated with their fatigue and sleep quality, whereas companionship (aOR 95% CI, 0.3-0.4) and higher caregiver cognition (aOR 95% CI, 0.1-0.2) were protective. In addition, sharing a room or bed or using methods that require listening for seizures were significantly related to sleep disturbance and fatigue in the caregivers. Conclusions: In rare epilepsies, pediatric sleep disturbances and night-time seizure monitoring are significantly associated with caregiver fatigue and poor sleep quality. In addition to the intense caregiving needs of children with rare epilepsies, fatigue and poor sleep quality in caregivers may contribute to or result from mental health problems.